Solid substrate fermentation (SSF) of sawdust by aspergillus niger for cellulase production - Mohd Amirul, Ghazali. (Universiti Malaysia Sarawak (UNIMAS), 2012)
Sawdust waste is one of the highly potential agricultural wastes that can be used as substrate for the production of cellulase via solid state fermentation. This research focuses on the relevant cultural condition for optimum cellulase production by the locally isolated Aspergillus niger using sawdust as substrate via solid state fermentation. The aim of this research is to study the optimum cellulase production using sawdust as substrate. Different levels of pH, initial moisture content and incubation time were set in order to assess their effects on cellulase production. The optimum pH for cellulase production was seen at pH 5.5 with 0.0463 IU/mL cellulase activity. Cultures moistened at 75% (v/w) gave 0.0669 IU/mL while the optimum incubation time was found between day 5 and day 7 where the highest cellulase production of 0.0523 IU/mL was attained. These preliminary results proved the feasibility of sawdust as potential substrate for cellulase production by the locally isolated Aspergillus niger.